2021
DOI: 10.1080/14613808.2021.1965564
|View full text |Cite
|
Sign up to set email alerts
|

The significance of music in early childhood education and care of toddlers in Finland: an extensive observational study

Abstract: The present study investigated the role of music education in early childhood education and care (ECEC) in relation to the daily activities of children ages one to three, i.e. toddlers (N = 918) in Finnish ECEC units (N = 327). A total of 23,142 random observations were conducted. The observations focused on children's involvement, emotional expressions, social orientations and interaction with their immediate caregiver. An independently conducted survey was used to evaluate music emphasis in groups to which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 59 publications
(56 reference statements)
0
5
0
1
Order By: Relevance
“…Moreover, it has been documented that high-quality visual arts pedagogy, concerns about perceived discrepancies between educational rhetoric and classroom application have been frequently raised (Lindsay, 2021). ECEC provides children with diverse opportunities to engage in arts, music, and other cultural aspects, fostering creative thinking, emotional expression, and play (Ruokonen et al, 2021).…”
Section: Creative Thinking Skillsmentioning
confidence: 99%
“…Moreover, it has been documented that high-quality visual arts pedagogy, concerns about perceived discrepancies between educational rhetoric and classroom application have been frequently raised (Lindsay, 2021). ECEC provides children with diverse opportunities to engage in arts, music, and other cultural aspects, fostering creative thinking, emotional expression, and play (Ruokonen et al, 2021).…”
Section: Creative Thinking Skillsmentioning
confidence: 99%
“…Pedagogy through Didactics can be interpreted as the creation of the contents and preconditions for children's learning where didactic skills are at the center [16]. These skills are, in particular, content knowledge, teaching methods management, and teaching planning [17]. Pedagogy through Expertise approach focuses on the teachers' professional knowledge, skills, and competence in cooperation, shared understanding of learning, and substance competence [1].…”
Section: Different Approaches To Pedagogy In Ecementioning
confidence: 99%
“…It is emphasized that music education in early childhood is not only an effective tool for children to develop their musical abilities but also to explore the world musically (Niland, 2009). In their study, Ruokonen, Tervaniemi, and Reunamo (2021) found that music in early childhood contributed significantly to children's learning and well-being in terms of participation in activities, developing positive emotions, and social cohesion. Ultimately, music is directly or indirectly included as an indispensable reality in early childhood education programs due to its benefits.…”
Section: Introductionmentioning
confidence: 99%